Plasticity of the P(junc) Promoter of ISEc11, a New Insertion Sequence of the IS1111 Family - Prosseda, Gianni (American Society for Microbiology, 2006)
We describe identification and functional characterization of ISEc11, a new insertion sequence that is widespread in enteroinvasive E. coli (EIEC), in which it is always present on the virulence plasmid (pINV) and very frequently also present on the chromosome. ISEc11 is flanked by subterminal 13-bp inverted repeats (IRs) and is bounded by 3-bp terminal sequences, and it transposes with target specificity without generating duplication of the target site. ISEc11 is characterized by an atypical transposase containing the DEDD motif of the Piv/MooV family of DNA recombinases, and it is closely related to the IS1111 family. Transposition occurs by formation of minicircles through joining of the abutted ends and results in assembly of a junction promoter (P(juncC)) containing a −10 box in the interstitial sequence and a −35 box upstream of the right IR. A natural variant of ISEc11 (ISEc11p), found on EIEC pINV plasmids, contains a perfect duplication of the outermost 39 bp of the right end. Upon circularization, ISEc11p forms a junction promoter (P(juncP)) which, despite carrying −10 and −35 boxes identical to those of P(juncC), exhibits 30-fold-greater strength in vivo. The discovery of only one starting point in primer extension experiments rules out the possibility that there are alternative promoter sites within the 39-bp duplication. Analysis of in vitro-generated transcripts confirmed that at limiting RNA polymerase concentrations, the activity of P(juncP) is 20-fold higher than the activity of P(juncC). These observations suggest that the 39-bp duplication might host cis-acting elements that facilitate the binding of RNA polymerase to the promoter.